2021
DOI: 10.1016/j.jse.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Combination of risk factors affecting retear after arthroscopic rotator cuff repair: a decision tree analysis

Abstract: Background: Several risk factors for postoperative retear after arthroscopic rotator cuff repair (ARCR) have been cited in a large number of reports; various combinations of these seem to be present in the clinical setting. Purpose: Using a combination model for decision tree analysis, we aimed to investigate the combination of risk factors that affect postoperative retear the most. Methods: A total of 286 patients who underwent magnetic resonance (MR) imaging at 6 months after surgery were included in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Circulation-derived lipid deposits in tendon extracellular matrix have been widely observed in nonfamilial hypercholesterolemia patients. The present research suggests that these deposits cause oxidative damage, persistent inflammatory cytokine production, obstructed tissue vascularity, 8 Retrospective cohort III ++++ + Satisfactory Cancienne et al, 2017 11 Retrospective cohort III ++++ + +++ Excellent Garcia et al, 2017 23 Retrospective cohort III ++++ ++ Good Harada et al, 2021 25 Retrospective cohort III ++++ +++ Good Kim et al, 2017 31 Retrospective cohort III ++++ ++ ++ Excellent Zheng et al, 2020 61 Retrospective cohort III ++++ ++ Good Jeong et al, 2018 30 Caseecontrol III ++++ + + Good Lee et al, 2020 38 Caseecontrol III +++ + ++ Good O'Donnell et al, 2020 46 Case series IV ++++ + +++ Excellent Park et al, 2020 49 Case series IV ++++ ++ ++ Excellent and reduced cholesterol efflux and matrix turnover by macrophages and tenocytes. 2,5,11,55 In a recent study by Li et al, 39 high cholesterol inhibited gene expression in tendon-derived stem cells, a newly identified resident cell population theorized to be responsible for tendon maintenance and repair.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Circulation-derived lipid deposits in tendon extracellular matrix have been widely observed in nonfamilial hypercholesterolemia patients. The present research suggests that these deposits cause oxidative damage, persistent inflammatory cytokine production, obstructed tissue vascularity, 8 Retrospective cohort III ++++ + Satisfactory Cancienne et al, 2017 11 Retrospective cohort III ++++ + +++ Excellent Garcia et al, 2017 23 Retrospective cohort III ++++ ++ Good Harada et al, 2021 25 Retrospective cohort III ++++ +++ Good Kim et al, 2017 31 Retrospective cohort III ++++ ++ ++ Excellent Zheng et al, 2020 61 Retrospective cohort III ++++ ++ Good Jeong et al, 2018 30 Caseecontrol III ++++ + + Good Lee et al, 2020 38 Caseecontrol III +++ + ++ Good O'Donnell et al, 2020 46 Case series IV ++++ + +++ Excellent Park et al, 2020 49 Case series IV ++++ ++ ++ Excellent and reduced cholesterol efflux and matrix turnover by macrophages and tenocytes. 2,5,11,55 In a recent study by Li et al, 39 high cholesterol inhibited gene expression in tendon-derived stem cells, a newly identified resident cell population theorized to be responsible for tendon maintenance and repair.…”
Section: Discussionmentioning
confidence: 62%
“…Meta-analysis was performed with results from 7 studies 4,23,25,30,31,46,49 reporting retear among DLD patients; Cancienne et al 11 were excluded because of patient overlap with O'Donnell et al 46 In total, 42,402 subjects were included, 52.8% of which had DLD. Patient age ranged from 45.3 to 84 years, with 54.0% males.…”
Section: Retearmentioning
confidence: 99%
“…Meta-analysis showed that rotator cuff retear was more likely with increasing body mass index (BMI) (WMD 0.52, 95% CI 0.23, 0.82; P < .001). A total of 7 studies 10,26,35,36,40,44,46,53 reported the impact of diabetes on rotator cuff healing. Meta-analysis showed that diabetes was a risk factor for retear after ARCR (OR 1.42, 95% CI 1.02, 1.97; P ¼ .04).…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
“…13,23,31,32 Predictive algorithms have been developed based on these risk factors and are based on anteroposterior tear size and age being more heavily weighted in providing a percentage risk of re-tear. 18,25 A summary of risk factors and their relative effects on re-tear rates are summarised in Table 1.…”
Section: Repair Techniquementioning
confidence: 99%